Journalism and Media Convergence - Russ-Mohl, Stephan (Media Convergence / Medienkonvergenz., 2013)
Journalism is under ever-increasing pressure, due in large part to the phenomenon of media convergence. Not only does media convergence redefine the tasks of journalists and newsrooms, it also re-shapes the business environments of media companies. In this book, international media practitioners and researchers describe and analyze the relationships between media convergence and advertising, public relations, social media and other areas of communication posing a challenge to journalism.